PENGARUH PEMUTIHAN PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KOTA PALEMBANG - Ferry, William; Sri, Dewi (Catholic University Musi Charitas, 2020)
The purpose of this study is to examine the impact of Sunset policy and Taxpayer Awareness of Taxpayer Compliance in Paying Vehicle Tax in Palembang City. The method used in this research is convenience sampling. The convenience sampling technique is done by taking respondents as a sample to whom happened to meet with the researcher. The population in this study is the motor vehicle taxpayers who live in the city of Palembang. The sample of research used in this research is 122 respondents. Analyzer used in this research is multiple linear regression analysis by using SPSS 21.0 program.,The results of this study indicate that vehicle tax bleaching and taxpayer awareness have a positive effect on taxpayer compliance in paying motor vehicle taxes.